Development of cellulose Nanofiber-based substrates for rapid detection of ferbam in kale by Surface-enhanced Raman spectroscopy. (15th June 2021) - Sun, Lin; Yu, Zhilong; Alsammarraie, Fouad K.; Lin, Min-Hui; Kong, Fanbin; Huang, Meizhen; Lin, Mengshi
Graphical abstract: Highlights: Cellulose nanofiber-based SERS wipers were fabricated on quartz papers. Wipers were coated with a mixture of AgNP and AuNS. A "drop-wipe-test" protocol was developed for rapid detection of pesticide residues. The detection limit for ferbam on kale leaves was 50 μg/kg. CNF-based SERS/wiper method can be use to detect pesticides in fresh produce. Abstract: This study developed a novel surface-enhanced Raman spectroscopy (SERS) method coupled with cellulose nanofiber (CNF)-based SERS wipers that were fabricated on quartz papers coated with a mixture of silver nanoparticle (AgNP) and gold nanostar (AuNS). A "drop-wipe-test" protocol was developed for rapid detection of pesticide residues in vegetables by SERS. Tremendously enhanced Raman scattering signals were obtained from the quartz/CNF/mixture (AgNP + AuNS) substrate, which were much higher than the paper/mixture (AgNP + AuNS) substrate. This method was used to detect ferbam on kale leaves within a few minutes and the detection limit was 50 μg/kg based on the PLS models (R 2  = 0.89). The enhancement factor of the SERS substrate was calculated to be ~ 10 4 with satisfactory reproducibility. Satisfactory SERS performance could be achieved within 1-month storage period. These results demonstrate that this CNF-based SERS/wiper method is a practical approach for rapid detection of chemical contaminants in fresh produce.